2001
DOI: 10.1139/x01-029
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of aspen forests in northeastern Minnesota, U.S.A., as related to stand composition and canopy structure

Abstract: Relationships among stand composition, stemwood productivity, and canopy structure were investigated for 55 study areas in northeastern Minnesota. Tree species composition among study areas was deliberately allowed to vary. Aspen, primarily quaking (Populus tremuloides Michx.) and to a lesser degree bigtooth (Populus grandidentata Michx.), was a significant component of every study area. The two most common associates were paper birch (Betula papyrifera Marsh.) and balsam fir (Abies balsamea (L.) Mill.). Produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 7 publications
4
11
1
Order By: Relevance
“…Models included interaction terms to account for differences in prediction slopes resulting from compositional effects (Edgar and Burk 2001). To characterize how tree species composition influences the susceptibility of carbon sequestration to insect defoliation (objective 3), we examined the reconstructed carbon accumulation, or annual aboveground carbon increment (C AI ), of trees >10.0 cm DBH from 1980 to 2008 and highlighted the varied disturbance history of sites and the impact of known defoliation events on carbon stocks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Models included interaction terms to account for differences in prediction slopes resulting from compositional effects (Edgar and Burk 2001). To characterize how tree species composition influences the susceptibility of carbon sequestration to insect defoliation (objective 3), we examined the reconstructed carbon accumulation, or annual aboveground carbon increment (C AI ), of trees >10.0 cm DBH from 1980 to 2008 and highlighted the varied disturbance history of sites and the impact of known defoliation events on carbon stocks.…”
Section: Discussionmentioning
confidence: 99%
“…Functional groups were defined as intolerant hardwoods of the genus Populus (PW), including P. tremuloides and occasionally P. balsamifera; tolerant hardwoods (HW), including A. rubrum, B. papyrifera, F. nigra, Tilia americana L., and U. americana; and tolerant softwoods (SW), including A. balsamea, P. glauca, and rarely P. strobus. Additionally, interaction terms were included between RD and the proportion of RD occupied by each functional group, as past investigations of compositional effects on productivity justify the inclusion of these terms (Edgar and Burk 2001). Plot composition was calculated as the proportion of plot RD occupied by each functional group (RD PW , RD HW , and RD SW ).…”
Section: Stand Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sites were not randomly selected; instead, we sampled a set of stands that met the aforementioned criteria -a rather small set due to the extensive regional harvest of 40-60 years old aspen mixedwoods. Site indices, tree densities, and basal areas were representative of fully stocked and productive P. tremuloides stands (Perala, 1977;Edgar and Burk, 2001). Stands had moderately well to poorly drained aqualf soils originating from clayey glaciolacustrine deposits or fine-textured glacial till.…”
Section: Study Areamentioning
confidence: 99%
“…This model showed that tree volume is a function of tree diameter and height. The relationship between tree volume and basal area has been discussed by many investigators (Edgar, 2001;Dean, 2004;Maltamo et al, 2006;Jensen et al, 2006). It is possible to predict stand basal area by a statistical model.…”
Section: Recent Progress and Future Directionsmentioning
confidence: 99%